BRINGING OUT THE “CAL” IN GLOCAL: SITUATING SUBCULTURE AND DIGITAL SUBCULTURES IN TURKISH YOUTH (Glocalism: Journal of Culture, Politics and Innovation, 2024)
In a globalized postmodern world, the metanarratives of modernity are contested and have been paving the way for a patchwork of cultures and subcultures. In this overarching context, subcultures represent values, norms and practices divergent, at the fringes of, or alternative to the dominant cultures, and thus are crucial to map the “cal” in glocal in a globalized world. In efforts to “make sense” of a postmodern glocal world, I argue that mapping the missing kaleidoscope of “cals” around the world is important more than ever. I examine in this article the youth subcultures specifically in the context of Turkey and discuss the potential of Turkish youth to form subcultures within the framework of the internet, and digital or “net subcultures”. To this end, the first part of the present study unpacks the concepts of “subculture”, “youth subculture” and digital “net subcultures” from a theoretical perspective. Next, I discuss why Turkish youth have been unable to form subcultural emergences throughout various historical periods. In the final section, I analyse whether technological innovations such as the internet, which allow for immediate access to different cultural forms, offer Turkish youth the possibility of creating nascent subcultures, and drawing from the particular contexts of the Gezi Protests in 2013 and the “Youth and Social Media Research” published that same year.
Keywords: Gezi protests; net subculture; digital subculture; Turkish youth; communication.